2016
DOI: 10.1016/j.bbr.2015.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of behavior and monoamine levels attributable to Lactobacillus plantarum PS128 in germ-free mice

Abstract: Probiotics, defined as live bacteria or bacterial products, confer a significant health benefit to the host, including amelioration of anxiety-like behavior and psychiatric illnesses. Here we administered Lactobacillus plantarum PS128 (PS128) to a germ-free (GF) mouse model to investigate the impact of the gut-brain axis on emotional behaviors. First, we demonstrated that chronic administration of live PS128 showed no adverse effects on physical health. Then, we found that administration of live PS128 signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(170 citation statements)
references
References 31 publications
4
146
1
3
Order By: Relevance
“…23,35 Two studies using Lactobacillus plantarum also found alleviated anxiety levels in mice after the intervention. 20,21 Bifidobacterium breve and Lactobacillus fermentum were used once each and showed anxiolytic effects. 30,36 Two studies using multi-strain probiotic combinations of L. rhamnosus + L. helveticus and B. longum + L. helveticus found reduced anxious behavior.…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…23,35 Two studies using Lactobacillus plantarum also found alleviated anxiety levels in mice after the intervention. 20,21 Bifidobacterium breve and Lactobacillus fermentum were used once each and showed anxiolytic effects. 30,36 Two studies using multi-strain probiotic combinations of L. rhamnosus + L. helveticus and B. longum + L. helveticus found reduced anxious behavior.…”
Section: Anxietymentioning
confidence: 99%
“…23,26,27,36,40 Two studies tested L. plantarum, but it only had an effect in mice with the early life stress of maternal separation. 20,21 One study used a multi-strain combination of B.…”
Section: 39mentioning
confidence: 99%
“…There are three suggested mechanisms for probiotics effects on mental health: The first way is referred to the probiotics ability in secretion of neurotransmitters such as gamma-aminobutyric acid (GABA), serotonin, catecholamines, and acetylcholine in the gut and notice brain function and affect behavior. Studies indicated that a considerable portion of brain chemicals like serotonin, GABA, dopamine, and acetylcholine produces in the intestines by gut microbiota [2,3,[7][8][9].…”
Section: Editorialmentioning
confidence: 99%
“…Studies showed that Lactobacillus plantarum (strain PS128) can cause positive changes in emotional behaviors and significantly reduce anxiety-like behaviors through increasing dopamine and serotonin, lowering stress hormone levels, and reducing inflammation [7].…”
Section: Editorialmentioning
confidence: 99%
“…In naïve mice, locomotor activity was increased, and anxiety-like behavior was decreased upon PS128 TM treatment. Prefrontal cortex analysis showed increased levels of dopamine and serotonin [11], suggesting that daily intake of PS128 TM exerts psychotropic effects that could reduce anxiety-like behavior and may be helpful in alleviating neuropsychiatric disorders by decreasing stress-related symptoms. Recently, evidence also showed that there are potentials for PS128 TM to improve cerebral dopamine-related symptoms in mice such as Tourette syndrome [12].…”
Section: Introductionmentioning
confidence: 99%